Increased Body Mass Index during Therapy for Childhood Acute Lymphoblastic Leukemia: A Significant and Underestimated Complication. (25th May 2015) - Atkinson, Helen C.; Marsh, Julie A.; Rath, Shoshana R.; Kotecha, Rishi S.; Gough, Hazel; Taylor, Mandy; Walwyn, Thomas; Gottardo, Nicholas G.; Cole, Catherine H.; Choong, Catherine S.
Abstract : Objective & Design . We undertook a retrospective review of children diagnosed with acute lymphoblastic leukemia (ALL) and treated with modern COG protocols ( n = 80 ) to determine longitudinal changes in body mass index (BMI) and the prevalence of obesity compared with a healthy reference population. Results . At diagnosis, the majority of patients (77.5%) were in the healthy weight category. During treatment, increases in BMI z -scores were greater for females than males; the prevalence of obesity increased from 10.3% to 44.8% ( P < 0.004 ) for females but remained relatively unchanged for males (9.8% to 13.7%, P = 0.7 ). Longitudinal analysis using linear mixed-effects identified associations between BMI z -scores and time-dependent interactions with sex ( P = 0.0005 ), disease risk ( P < 0.0001 ), age ( P = 0.0001 ), and BMI z -score ( P < 0.0001 ) at diagnosis and total dose of steroid during maintenance ( P = 0.01 ) . Predicted mean BMI z -scores at the end of therapy were greater for females with standard risk ALL irrespective of age at diagnosis and for males younger than 4 years of age at diagnosis with standard risk ALL. Conclusion . Females treated on standard risk protocols and younger males may be at greatest risk of becoming obese during treatment for ALL. These subgroups may benefit from intervention strategies to manage BMI during treatment for ALL.